Characterization of mutations conferring streptomycin resistance in \(Mycobacterium tuberculosis\) in Vietnam - Quang Huy, Nguyen; Banuls, Anne-Laure; Van Anh, Nguyen Thi (Academia Journal of Biology, 2023)
Recently, World Health Organization (WHO) has listed streptomycin (STR) in the list of second-line injectable drugs in the multidrug-resistant tuberculosis (MDR-TB) regimens and may replace amikacin under the same conditions. Nevertheless, molecular characterizations associated with STR resistance in the Mycobacterium tuberculosis population have not been fully investigated in Vietnam. The present study aimed to explore the variation and frequency of mutations in rpsL and rrs genes and their relationship with drug-resistant patterns and M. tuberculosis genotypes in 163 STR-resistant strains from Vietnam. The mutation frequency of the rpsL and rrs genes were 62% and 20.9%, respectively, and the mutation combination in both genes covered 81% of STR-resistant strains. The most prevalent mutations included rpsL Lys43Arg (38.7%), Lys88Arg (19.6%), rrs A514C (10.4%) and A517C (5.5%). Thus, sequence analysis of rpsL and rrs exhibited a sensitivity of 81% and specificity of 100% for the prediction of STR resistance in Vietnamese M. tuberculosis strains. The prevalence of STR-resistant mutations in double, triple and quadruple resistance strains was significantly different, compared with mono STR-resistant ones. Similarly, mutation frequency associated with STR resistance in MDR strains was significantly higher than that in non-MDR strains. In addition, the lineage 2 genotype was significantly correlated with a high rate of STR resistance-conferring mutation, as well as the mutation rpsL Lys43Arg (P < 0.01), while the lineage 1 genotype was associated with a low rate of STR resistance-conferring mutation and rrs mutations (P<0.05). In conclusion, sequence analysis may be useful for the rapid detection of STR resistance in MDR M. tuberculosis strains, which in turn could contribute to better control strategies of TB in Vietnam. Other molecular mechanisms associated with STR resistance in STR-resistant strains without mutations in the rpsL and rrs genes need to be further investigated.